Antioxidant responses and lipid peroxidation in Mozambique tilapia (Oreochromis mossambicus) exposed to phenol and m-cresol - Varadarajan, Remya; Philip, Babu (Indian Journal of Fisheries, 2016)
The present study evaluated phenol and m-cresol induced oxidative stress responses in the teleost fish Oreochromis mossambicus in a semi-static test system in which water was renewed every 24 h. Fishes were exposed to sublethalÂ (1/10 of LC50/96 h) concentration of phenol (3.12 mg l-1) and m-cresol (2.2 mg l-1) for a period of 21 days. Significant increases in catalase (CAT) and superoxide dismutase (SOD) activities in gills, liver and kidney of treated groups represent an adaptive response to free radical toxicity. Reduction in enzyme activity shows that all reactive oxygen species (ROS) are not being quenched. Glutathione-S-transferase (GST) activity was found to be highly elevated in liver which may be due to its important role in the detoxification of xenobiotics. Total reduced glutathione glutathiore peroxidase (GSH) level was found to be highest in liver which may be an adaptive mechanism to oxidative stress. An increased hydroperoxide (HP) level was observed in liver, kidney and muscle of both the treated groups which may be attributed to the decreased glutathione peroxidase (GPx) activity observed. Increased malondialdehyde (MDA) levels in gills and liver indicates that elevated antioxidant enzyme activities were not efficient enough to prevent lipid peroxidation in these tissues. Taken as a whole, the present results seem to implicate that phenolic compounds are potent mediators of free radical generation in fish.